Machine learning applied to pore-space geometry in sandstones: a tool for evaluating grain-scale similarity. Issue 1 (2022) - Hall, Alexander; Gillespie, Martin; Everett, Paul; Christodoulou, Vyron; Walsh, Jo
No abstract available